Observing the user experience : a practitioner's guide to user research - Kuniavsky, Mike.; Goodman, Elizabeth, 1976-; Moed, Andrea (Amsterdam ; Boston : Morgan Kaufmann, 2012)
The gap between who designers and developers imagine their users are, and who those users really are can be the biggest problem with product development. This title helps you to bridge that gap to understand what your users want and need from your product, and whether they'll be able to use what you've created.
Machine generated contents note: Part I: Why Research is Good and How It Fits Into Product Development 1. Typhoon: A Fable 2. Do a Usability Test Now! 3. Balancing Needs Through Iterative Development 4. The User Experience Part II: User Experience Research Techniques 5. The Research Plan 6. Universal tools: Recruiting and Interviewing 7. User Profiles 8. Contextual Inquiry, Task Analysis, Card Sorting 9. Focus Groups 10. Usability Tests 11. Surveys 12. Ongoing Relationship 13. Log Files and Customer Support 14. Competitive Research 15. Others' Hard Work: Published Information and Consultants 16. Emerging Techniques Part III: Communicating Results 17. Reports and Presentations 18. Creating a User-Centered Corporate Culture Appendices A. The Budget Research Lab B. Common Survey Questions C. Observer Instructions Bibliography Index About the Author.
Includes bibliographical references (pages 571-576) and index.
Keywords: User-centered system design; Observation (Scientific method)